1998
DOI: 10.1103/physrevb.57.4943
|View full text |Cite
|
Sign up to set email alerts
|

Optical transmission spectroscopy of switchable yttrium hydride films

Abstract: The optical transmission of the recently discovered switchable yttrium hydride films is determined spectroscopically as a function of hydrogen content. This is done during electrochemical loading of Pd-capped Y film electrodes, thereby continuously changing the hydrogen concentration. The effect of the Pd cap layer on the film transmission is determined from measurements on a series of films with varying Pd layer thickness. The results are in good agreement with transmission measurements of in situ gas phase l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
68
0
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 113 publications
(72 citation statements)
references
References 17 publications
2
68
0
2
Order By: Relevance
“…6,7 Recently den Broeder et al 8 presented an optical method to monitor the lateral migration of hydrogen in Y, exploiting the intrinsic concentration dependent optical properties of the Y-H system. 9 Especially the progression of the boundaries separating the various stable hydride phases can easily be detected as discontinuities in the optical contrast.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…6,7 Recently den Broeder et al 8 presented an optical method to monitor the lateral migration of hydrogen in Y, exploiting the intrinsic concentration dependent optical properties of the Y-H system. 9 Especially the progression of the boundaries separating the various stable hydride phases can easily be detected as discontinuities in the optical contrast.…”
mentioning
confidence: 99%
“…The lateral migration of hydrogen in vanadium away from the Pd-covered region can easily be monitored optically in the Y indicator layer as the various yttrium hydride phases formed at different hydrogen concentrations, exhibit characteristic optical properties. 9,11 For example, the front corresponding to the coexisting ␣ and ␤ phases is clearly identified as a discontinuous change in transmission and reflection. 8 11,12 In the following we call this optical feature the ''␤-front'' or simply the front and its position x f .…”
mentioning
confidence: 99%
“…Electrochemical loading offers a double advantage: the concentration of hydrogen in the film can be controlled accurately, and extremely low pressures can be achieved. 7,8 The adsorbed hydrogen diffuses into the material; the concentration of hydrogen in the film, x, ͑hydrogen/metal atomic ratio͒ is proportional to the charge transferred in the electrochemical reaction. 7 With the galvanostatic intermittent titration technique ͑GITT͒, 9 the equilibrium potential U e , which is measured in open circuit after a current pulse, provides us, via the Nernst equation, with the equivalent hydrogen pressure p H 2 :…”
mentioning
confidence: 99%
“…It is a further development of the optical method presented by Den Broeder et al 5 to monitor the lateral migration of hydrogen in Y, exploiting the intrinsic concentration dependent optical properties of the Y-H system. 6 Electromigration studies on thin film YH x samples demonstrated that H in Y behaves like a negatively charged particle, 5,7 opening the possibility to work with electrodiffusion waves. In the presence of a static electric field E a charged particle experiences an additional force, leading to electrodiffusion waves which are solutions of a modified diffusion equation:…”
Section: ͑1͒mentioning
confidence: 99%
“…The lateral migration of hydrogen in Y away from the Pdcovered region can easily be monitored optically, as different yttrium-hydride phases are formed at different hydrogen concentrations, exhibiting characteristic optical properties. 6,11 Figure 1 depicts below the schematical sample design two vanadium samples of 50 nm and 100 nm thickness. The images are recorded after an exposure of 3 h in a hydrogen atmosphere of 1 mbar at 473 K. The front separating the ␣ from the ␤ phase is clearly identified from a discontinuous change in reflection.…”
Section: ͑3͒mentioning
confidence: 99%